2009
DOI: 10.1124/jpet.109.154583
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Talk between Protein Kinase A and Mitogen-Activated Protein Kinases Signalling in the Adaptive Changes Observed during Morphine Withdrawal in the Heart

Abstract: Our previous studies have shown that morphine withdrawal induced an increase in the expression of protein kinase (PK) A and mitogen-activated extracellular kinase (MAPK) pathways in the heart during morphine withdrawal. The purpose of the present study was to evaluate the interaction between PKA and extracellular signal-regulated kinase (ERK) signaling pathways mediating the cardiac adaptive changes observed after naloxone administration to morphine-dependent rats. Dependence on morphine was induced by a 7-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…In the heart after 90 min, there is an increase in TH protein levels, TH phosphorylation at Ser40, as well as the PKA catalytic subunit (Almela et al 2008). The increases in TH protein levels and TH phosphorylation at Ser40 are blocked by infusion of a PKA inhibitor HA-1004 (Almela et al 2008;Almela et al 2009a;Almela et al 2009b). Acute treatment of mice with haloperidol increases the phosphorylation of TH at both Ser31 and Ser40 in the striatum (Hakansson et al 2004).…”
Section: Ser40mentioning
confidence: 99%
“…In the heart after 90 min, there is an increase in TH protein levels, TH phosphorylation at Ser40, as well as the PKA catalytic subunit (Almela et al 2008). The increases in TH protein levels and TH phosphorylation at Ser40 are blocked by infusion of a PKA inhibitor HA-1004 (Almela et al 2008;Almela et al 2009a;Almela et al 2009b). Acute treatment of mice with haloperidol increases the phosphorylation of TH at both Ser31 and Ser40 in the striatum (Hakansson et al 2004).…”
Section: Ser40mentioning
confidence: 99%
“…But chronic morphine treatment showed to decline baseline cardiovascular parameters MAP and HR. During morphine withdrawal, when naloxone was injected in morphinetreated rats, MAP and HR (26), systolic and diastolic BP were all attenuated (27). Evidences are in fader of the fact that smoking causes induced HR, SBP, DBP, and MBP (28).The increased BP following administration of nicotine may possibly be due to the induced PRA level (29).…”
Section: Discussionmentioning
confidence: 99%
“…To further investigate the role of ouabain-induced cAMP on rabbit atria, we examined the effects of ouabain and 8-Bromo-cAMP on atrial ET-1 secretion and determined that secretion was significantly increased by both agents and blocked by the PKA inhibitor H-89 and by the MAPK/ERK inhibitor PD98059. cAMP-dependent PKA signaling is related to the MAPK/ERK signaling pathway [ 7 ]. In previous work we showed that the MAPK/ERK signaling pathway is involved in the regulation of ouabain-induced atrial ET-1 secretion and to promotes atrial ANP release[ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is required for the activation of protein kinase A (PKA). The PKA signaling pathway is one of the most important cellular signaling pathways but it has also been shown to promote mitogen-activated protein kinase (MAPK)/extracellular signal-regulated kinase (ERK) phosphorylation in the heart during morphine withdrawal [ 7 ].…”
Section: Introductionmentioning
confidence: 99%